PENGARUH FAKTOR LINGKUNGAN TERHADAP HASIL BELAJAR SISWA KELAS XI IPS 1 PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 1 BANDAR PETALANGAN KABUPATEN PELALAWAN - Alimun Alimun; Caska Caska; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : focus of this study is the low learning outcomes of IX IPS 1 students based on the daily test results where the average of student learning outcomes is 72, but the value is still below the standard value of 75. The formulation of the problem of this research is whether the school environment, partially and simultaneously effect to the students' learning outcomes in Economics lesson at SMAN 1 Bandar Petalangan, Pelalawan District. The population in this study is the sum of the overall object that will be studied, the students of class X and XI IPS SMAN 1 Bandar Petalangan who gets economics lessons, amounted to 240 people. The sample of this research is the students of Class XI IPS 1 SMAN 1 Bandar Petalangan Pelalawan District in Year 2018/2019 consisting of 40 students. Data analysis using quantitative descriptive with multiple regression model. Partial test results of school environmental factors significantly influence learning outcomes of student on XI IPS 1 SMAN 1 Petalangan Pelalawan District. Family environment also affects the results of learning outcomes of class XI IPS 1 SMAN 1 Petalangan Pelalawan District. The simultaneously results state that the school environment and family environment have a positive and significant impact on the learning outcomes of students of class XI IPS 1 SMAN 1 Petalangan Pelalawan District.Keywords: Environment and Outcomes.